Editor's Choice – International Variations and Sex Disparities in the Treatment of Peripheral Arterial Occlusive Disease: A Report from VASCUNET and the International Consortium of Vascular Registries. (December 2020) - Behrendt, Christian-Alexander; Sigvant, Birgitta; Kuchenbecker, Jenny; Grima, Matthew J.; Schermerhorn, Marc; Thomson, Ian A.; Altreuther, Martin; Setacci, Carlo; Svetlikov, Alexei; Laxdal, Elin H.; Goncalves, Frederico Bastos; Secemsky, Eric A.; et al.
Abstract : Objective: The aim of this study was to determine sex specific differences in the invasive treatment of symptomatic peripheral arterial occlusive disease (PAOD) between member states participating in the VASCUNET and International Consortium of Vascular Registries. Methods: Data on open surgical revascularisation and peripheral vascular intervention (PVI) of symptomatic PAOD from 2010 to 2017 were collected from population based administrative and registry data from 11 countries. Differences in age, sex, indication, and invasive treatment modality were analysed. Results: Data from 11 countries covering 671 million inhabitants and 1 164 497 hospitalisations (40% women, mean age 72 years, 49% with intermittent claudication, 54% treated with PVI) in Europe (including Russia), North America, Australia, and New Zealand were included. Patient selection and treatment modality varied widely for the proportion of female patients (23% in Portugal and 46% in Sweden), the proportion of patients with claudication (6% in Italy and 69% in Russia), patients' mean age (70 years in the USA and 76 years in Italy), the proportion of octogenarians (8% in Russia and 33% in Sweden), and the proportion of PVI (24% in Russia and 88% in Italy). Numerous differences between females and males were observed in regard to patient age (72 vs. 70 years), the proportion of octogenarians (28% vs. 15%), proportion of patients with claudication (45% vs. 51%), proportion of PVI (57% vs. 51%), and length of hospital stay (7 days vs. 6 days). Conclusion: Remarkable differences regarding the proportion of peripheral vascular interventions, patients with claudication, and octogenarians were seen across countries and sexes. Future studies should address the underlying reasons for this, including the impact of national societal guidelines, reimbursement, and differences in health maintenance.